To "Hamlet" or Not to "Hamlet: Notes on an Arts Secondary School Students’ "Hamlet" - Ciobanu, Estella; Trifan Enache, Dana (Multicultural Shakespeare: Translation, Appropriation and Performance, 2020)
This article discusses a 2018 theatrical production of Hamlet with Romanian teenage arts students, directed by one of the article’s authors, actress and academic Dana Trifan Enache. As an artist, she believes that the art of theatre spectacle depends pre-eminently on the actors’ enactment, and hones her students’ acting skills and technique accordingly. The other voice in the article comes from an academic in a cognate discipline within the broad field of arts and humanities. As a feminist and medievalist, the latter has investigated the political underside of representations of the body in religious drama, amongst others. The analytic duo reflects as much the authors’ different professional formation and academic interests as their asymmetrical positioning vis-à-vis the show as respectively the play’s director and one of its spectators. Their shared occupational investment, teaching to form and hone highly specialized professional skills, and shared object of professional interest (broadly conceived), text interpretation, account nevertheless for the possibility of fruitful interdisciplinary reflection on the 2018 Hamlet. This in-depth analysis of the circumstances of the performance and technical solutions it sought challenges stereotyped dismissals of a students’ Hamlet as superannuated, flimsy or gratuitously provocative. Furthermore, a gender-aware examination of the adaptation’s original handling of characters and scenes indicates unexpected cross-cultural and diachronic commonalities between the dramatic world of the 2018 Romanian production of Hamlet and socio-cultural developments emergent in pre-Shakespearean England.